2017
DOI: 10.3847/1538-4357/aa7849
|View full text |Cite
|
Sign up to set email alerts
|

Physics of Galactic Metals: Evolutionary Effects due to Production, Distribution, Feedback, and Interaction with Black Holes

Abstract: We ask how the inclusion of various physical heating processes due to the metal content of gas affect the evolution of central massive galaxies and compute a suite of cosmological hydrodynamical simulations that follow these systems and their supermassive black holes. We use a smoothed particle hydrodynamics code with a pressure-entropy formulation and a more accurate treatment of the metal production, turbulent diffusion and cooling rate based on individual element abundances. The feedback models include (1) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(121 citation statements)
references
References 148 publications
(194 reference statements)
6
115
0
Order By: Relevance
“…Additionally, the investment in computational time for higher-resolution simulations appears justifiable only after an improvement of contemporary models, which in some respects suffer from significant deficits. For instance, simulations on larger spatial scales (out to R eff ) by Hirschmann et al (2013) and Choi et al (2017) always predict strongly positive age gradients in massive (log(M ,T /M )>10) galaxies (Hirschmann et al 2015), which indicates that better prescriptions or additional physical processes need to be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the investment in computational time for higher-resolution simulations appears justifiable only after an improvement of contemporary models, which in some respects suffer from significant deficits. For instance, simulations on larger spatial scales (out to R eff ) by Hirschmann et al (2013) and Choi et al (2017) always predict strongly positive age gradients in massive (log(M ,T /M )>10) galaxies (Hirschmann et al 2015), which indicates that better prescriptions or additional physical processes need to be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…3). This high rate of BH accretion in turn results in a phase of significant gas heating and ejection, so that the total galaxy stellar mass remains constant after z ∼ 1, as in-situ star formation is strongly suppressed due to the lack of available dense gas (see also Choi et al 2017). Also the warm gas fractions are strongly reduced after z ∼ 1, causing subsequent fluctuations in all three irregularity parameters.…”
Section: Galaxy 0094mentioning
confidence: 99%
“…The sets of simulated galaxies, examined in this work, have been introduced by Hirschmann et al (2017) and Choi et al (2017), and we urge readers to consult these works for more details beyond the brief summary we provide here.…”
Section: Simulation Samplementioning
confidence: 99%
“…They can reproduce the observational results and compare the X-ray properties in detail [5][6][7][8]. References [5,6] applied 2D high-resolution hydro simulations and considered stellar feedback, dynamical (rotation), and structural (flattening) parameters as well as AGN feedback, and References [7,8] applied 3D cosmological simulations. While the differences among different simulations and different parameters/recipes are to yet be understood, in general they can reproduce the observed relations among L X,GAS , T GAS , M TOTAL (or M within 5 Re).…”
Section: Comparison With Simulationsmentioning
confidence: 99%
“…Recent numerical simulation studies [5][6][7][8] have further attempted to reproduce the observed scaling relations, in order to constrain the physical mechanisms that shape the hot ISM.…”
Section: X-ray Scaling Relationsmentioning
confidence: 99%